Serial profile of flow-mediated dilatation in primigravida for prediction of preeclampsia and gestational hypertension - Anita S. Malhotra; Poonam Goel; Archana Chaudhary; Suman Kochhar; Gurjit Kaur; Anumeha Bhagat (Taylor & Francis Group, 2018)
Objective: Assessment of endothelial dysfunction for prediction of gestational hypertension/preeclampsia (GH/PE). Methods: Serial assessment of flow-mediated vasodilatation (FMD) of brachial artery was done in first, second, and third trimesters, and within 6 weeks of delivery in primigravida (n = 654). Logistic regression was used to assess the predictive value of FMD for the development of GH/PE. Results: Significant fall in FMD was observed from first trimester to third trimester but decrease in FMD in GH/PE group (57%) was more marked as compared to normal (39%) (p < 0.01). FMD (third trimester) was able to predict the development of GH/PE (OR = 1.303; 95% CI 1.088-1.562; p = 0.004). Conclusions: FMD can be used as a non-invasive marker to predict the development of GH/PE.